2017
DOI: 10.1074/mcp.ra117.000230
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Salmonella Type III Effector by Quantitative Secretome Profiling

Abstract: serovar Typhimurium is arguably one of the most studied bacterial pathogens and successful infection requires the delivery of its virulence factors (effectors) directly into host cells via the type III secretion systems (T3SSs). Central to pathogenesis, these effector proteins have been subjected to extensive studies over the years. Nevertheless, whether additional effectors exist remains unclear. Here we report the identification of a novel T3SS effector STM1239 (which we renamed SopF) via quantitative secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…Six mutants were significantly attenuated for spleen colonization. In addition, Cheng et al have recently identified a novel SPI-1 effector, SopF that is required for Salmonella virulence in mice using a similar proteomic approach (48).…”
Section: Discussionmentioning
confidence: 99%
“…Six mutants were significantly attenuated for spleen colonization. In addition, Cheng et al have recently identified a novel SPI-1 effector, SopF that is required for Salmonella virulence in mice using a similar proteomic approach (48).…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, our group undertook quantitative secretome profiling to catalogue Salmonella effectors delivered by SPI-1 T3SS [ 40 ]. By using a SPI-1-deficient mutant (∆ invA ) as a control, we identified STM1239 (which we renamed SopF) as a novel substrate of T3SS.…”
Section: Proteomic Tools Assist In the Study Of Bacterial Virulencmentioning
confidence: 99%
“…The use of genome mining in this context will only be useful if information (e.g., homology regions, structural information) about effectors are available. The use of techniques such as proteomics along with bioinformatic mining/analysis has been suggested as more useful tools in combination to identify effectors (Na et al, 2015; Cheng et al, 2017). For example, in recent studies, proteomics have been used to identify novel effectors in Salmonella .…”
Section: The Impossible Made Possible?mentioning
confidence: 99%